Implementation of Administrative Sanctions Against Notaries for Formal Negligence in Making Authentic Deeds - Chairil, Chairil; widayati, widayati (Jurnal Konstatering, 2025)
This study aims to examine the form of formal negligence committed by the Notary WP in making the Deed of Lease Agreement Number 97 of 2021, analyze the application of administrative sanctions by the Notary Supervisory Board, and evaluate the legal consequences of issuing a copy of the deed based on the minutes that were not signed by all parties. This study uses a normative and empirical legal approach. Data were obtained through literature studies, legal documentation, and interviews with the Notary and the Kolaka Regional Supervisory Board. Based on the results of the study, it was found that the Notary issued a copy of the deed without a complete signature on the minutes, which is a violation of Article 44 paragraph (5) of the Notary Law. Administrative sanctions in the form of temporary suspension for three months were imposed by the Central Supervisory Board as a form of guidance. Legally, the deed no longer has the force of an authentic deed and only stands as a deed underhand, which can create legal uncertainty and reduce the credibility of the Notary.